Apoptosis antagonizing transcription factor expression and its validation as a potential diagnostic and prognostic biomarker in oral squamous cell carcinoma - Abudourousuli, Ainiwaerjiang; Aierken, Zumulaiti; Mamuti, Hasiyati; Yimamu, Tuxunayi; Da, Chengli (Frontiers in Oncology, 2025)
BackgroundOral squamous cell carcinoma (OSCC) is characterized by a high degree of malignancy and poor prognosis. This study aimed to investigate the expression of apoptosis antagonizing transcription factor (AATF) in OSCC, examine its correlation with clinicopathological features, assess its prognostic implications, and explore its potential role in OSCC progression.MethodsExpression profiles and clinical data of OSCC patients were obtained from The Cancer Genome Atlas (TCGA). Immunohistochemical analysis on tissue microarrays was performed to assess AATF expression in OSCC. Functional enrichment analyses were conducted to identify potential signaling pathways and biological functions associated with AATF. Logistic regression analyses were employed to evaluate the relationship between AATF expression and clinicopathological features. Immune cell infiltration was assessed using single-sample gene set enrichment analysis (ssGSEA). The prognostic value of AATF was determined using Kaplan-Meier and Cox regression analyses. A nomogram was developed to predict overall survival (OS) rates at one, three-, and five years post-cancer diagnosis. Validation of AATF expression was performed using quantitative real-time PCR (qRT-PCR)ResultsAATF was significantly overexpressed in OSCC, and high AATF expression correlated with adverse clinicopathological features, including histologic grade and lymph node metastasis. Functional enrichment analysis revealed several enriched pathways, including epidermis development, immunoglobulin complex, antigen binding and IL-17 signaling pathway. Notably, AATF overexpression was negatively correlated with the infiltration levels of mast cells, interdigitating dendritic cells and Th 17 cells. High AATF expression significantly predicted poorer overall survival (OS) and disease-specific survival (DSS). Multivariate Cox analysis confirmed AATF as an independent negative prognostic marker of OS. Validation via qRT-PCR confirmed the overexpression of AATF in OSCC tissues.ConclusionElevated expression of AATF in OSCC correlates with adverse clinicopathological features and negatively impacts immune cell infiltration. High AATF levels serve as an independent marker of poor OS and DSS. These findings support AATF as a valuable prognostic biomarker and a potential therapeutic target in OSCC, warranting further investigation.